Phosphorus Limitation Enhances Diazotroph Zinc Quotas - Wang, Xuechao; Browning, Thomas J.; Achterberg, Eric P.; Gledhill, Martha (Frontiers in Microbiology, 2022)
Trichodesmium spp. is a colonial diazotrophic cyanobacterium found in the oligotrophic (sub)tropical oceans, where dissolved inorganic phosphorus (DIP) can be depleted. To cope with low P concentrations, P can be scavenged from the dissolved organic P (DOP) pool. This requires the deployment of multiple enzymes activated by trace metals, potentially enhancing metal requirements under stronger P limitations. To test this, we grew Trichodesmium under trace-metal-controlled conditions, where P was supplied as either DIP or DOP (methylphosphonic acid). Mean steady-state biomass under the DOP treatment was only 40% of that grown under equivalent DIP supply, carbon normalized alkaline phosphorus activity was elevated 4-fold, and the zinc (Zn)–carbon ratio was elevated 3.5-fold. Our finding matches the known, dominant Zn requirement across a diversity of enzymes involved in P stress responses and supports an important interaction in the oceanic cycles of these two nutrients.